2013
DOI: 10.1016/j.jns.2013.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Frequent inaccuracies in ABCD2 scoring in non-stroke specialists' referrals to a daily Rapid Access Stroke Prevention service

Abstract: The 'accuracy' of age, blood pressure, clinical features, duration and diabetes (ABCD 2 ) scoring by non-stroke specialists referring patients to a daily Rapid Access Stroke Prevention (RASP) service is unclear, as is the accuracy of ABCD 2 scoring by trainee residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Two studies 10,20 provided sufficient information to calculate PPVs according to two referral routes (GP or ED doctor) and a further study provided information on PPVs for referrals purely from GPs. 27 One study gave PPVs predominantly from Banerjee et al (2009) 11 Bradley et al (2013) 12 Dutta et al (2015) 14 Dutta (2016) 15 Fallon et al (2006) 16 Ferro et al (1996) (GP route) 10 Ferro et al (1996) (ED route) 10 Fonseca and Canhão (2011) 26 Karunaratne et al (1999) 17 Lasserson et al (2015) 27 Lavallée et al (2007) 18 Lee and Frayne (2015) 19 Magin et al (2013) (GP route) 20 Magin et al (2013) (ED route) 20 Martin et al (1997) 25 Murray et al 2007 an ED setting, 16 whereas all other studies appeared to have largely comprised referrals from GPs. With the exception of one small study, 10 the PPVs appear lower in GP referrals than in referrals from ED doctors ( Table 1; Figures 2 and 3).…”
Section: Influence Of Referral Source and Referral Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies 10,20 provided sufficient information to calculate PPVs according to two referral routes (GP or ED doctor) and a further study provided information on PPVs for referrals purely from GPs. 27 One study gave PPVs predominantly from Banerjee et al (2009) 11 Bradley et al (2013) 12 Dutta et al (2015) 14 Dutta (2016) 15 Fallon et al (2006) 16 Ferro et al (1996) (GP route) 10 Ferro et al (1996) (ED route) 10 Fonseca and Canhão (2011) 26 Karunaratne et al (1999) 17 Lasserson et al (2015) 27 Lavallée et al (2007) 18 Lee and Frayne (2015) 19 Magin et al (2013) (GP route) 20 Magin et al (2013) (ED route) 20 Martin et al (1997) 25 Murray et al 2007 an ED setting, 16 whereas all other studies appeared to have largely comprised referrals from GPs. With the exception of one small study, 10 the PPVs appear lower in GP referrals than in referrals from ED doctors ( Table 1; Figures 2 and 3).…”
Section: Influence Of Referral Source and Referral Criterionmentioning
confidence: 99%
“…As such, it was not possible to compute sensitivity or specificity. This means that it was also not possible to interpret whether high predictive values were associated with Banerjee et al (2009) 11 Bradley et al (2013) 12 Dutta et al (2015) 14 Dutta (2016) 15 Fallon et al (2006) 16 Ferro et al (1996) (GP route) 10 Ferro et al (1996) (ED route) 10 Fonseca and Canhão (2011) (weekly clinic) 34 Fonseca and Canhão (2011) (daily clinic) a, 34 Freitas et al (2010) a, 35 Hall and Oczkowski (2010) a, 36 Karunaratne et al (1999) 17 Kleinig et al (2013) a, 24 Lasserson et al (2015) 27 Lavallée et al (2007) 18 Lebus et al (2012) a, 29 Lee and Frayne (2015) 19 Magin et al (2013) (GP route) 20 Magin et al (2013) (ED route) 20 Martin et al…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, as per its original purpose, use of the score by nonexperts is encouraged, including with financial incentives to fast-track patients with ABCD2 score $4 to clinics in some countries. 8 Nurses now perform initial patient triage in about 30% of TIA clinics using the ABCD2 score, 11 but several studies indicate that the agreement for ABCD2 scoring between nonspecialists and vascular neurologists is only fair, 12,49,50 and the score has low sensitivity and specificity when used by nonspecialists in the community 12 or emergency department, 34 irrespective of the cutpoint used. 50 These limitations 50 have led to withdrawal of recommendation of the ABCD2 score from the Canadian stroke guidelines.…”
Section: 44mentioning
confidence: 99%
“…8 However, the ABCD2 score may have limitations for identifying important categories of patients, e.g., those with tight carotid stenosis or atrial fibrillation (AF), 9,10 and may not perform as well in the field as suggested in early reports and guidelines. 11,12 In view of these doubts, we assessed all available data to determine the extent to which the ABCD2 score had been tested in stroke prevention in circumstances in which guidelines now promote its use, and its ability to predict stroke recurrence in patients at high ($4) and low (,4) risk of stroke; differentiate patients with mimics from true stroke/TIA; identify carotid stenosis or AF; and estimate its effect on proportions of patients entering fast-or slow-track assessment in a typical stroke prevention service per 1,000 patients assessed.…”
mentioning
confidence: 99%
“…10 The ABCD 2 score is also less accurate when calculated by nonstroke physicians. 52 Given the doubts in the ABCD 2 score's ability to differentiate low-and high-risk stroke patients or those requiring urgent intervention for carotid stenosis or atrial fibrillation, 53 additional scores have been developed. Coutts and colleagues devised a more complex ABCD 2 þ MRI scoring system in which the ABCD 2 score items were retained and two MRI items added (presence of a diffusion weighted imaging [DWI] lesion and intracranial vessel occlusion).…”
Section: Risk Stratification In Tia: Getting It Rightmentioning
confidence: 99%